Effects of Erythropoietin in White Adipose Tissue and Bone Microenvironment - Suresh, Sukanya; Lee, Jeeyoung; Noguchi, Constance Tom (Frontiers in Cell and Developmental Biology, 2020)
Erythropoietin (EPO) is expressed primarily in fetal liver and adult kidney to stimulate red blood cell production. Erythropoietin receptor (EPOR) expression is not restricted to erythroid progenitor cells and non-erythroid EPO activity includes immune response and bone remodeling. In adult mice, EPO stimulated erythropoiesis results in elevated hematocrit and concomitant bone loss with increased osteoclast activation, particularly at high dose EPO. Other EPO associated responses include reduced inflammation and loss of fat mass with high-fat diet feeding, especially in male mice. While EPO exhibited a sex-dimorphic response in regulation of fat mass and inflammation in obese mice, EPO stimulated erythropoiesis as well as erythropoietin associated bone loss was comparable in males and females. EPO administration in young mice and in obese mice resulted in bone loss without increasing osteoclasts suggesting potential osteoclast independent mechanism, while loss of endogenous EPO decreased bone development and maintenance. Ossicle formation of bone marrow stromal cell transplants showed that EPO directly regulates the balance between osteogenesis and adipogenesis. Therefore, during development endogenous EPO contributes to normal bone development and in maintaining the balance between osteogenesis and adipogenesis in bone marrow stromal cells, while EPO treatment in mice to increase erythropoiesis also promotes bone loss, decreases bone marrow adipogenesis and increases osteoclast activity. These observations in mouse models suggest that the most prevalent use of EPO to treat anemia associated with chronic kidney disease may compromise bone health and increase fracture risk, especially at high dose.